A field study investigating running distance and affect of field hockey players in collective team collapse situations - Wergin, V. V.; Zimanyi, Z.; Beckmann, J. (International Journal of Sport and Exercise Psychology, 2021)
Causes of collective team collapse, the phenomenon when a team experiences a sudden and extreme underperformance from which it cannot recover, remain unexplained. Existing qualitative research indicates an association between negative affect and collective team collapse. To measure a collective team collapse occurring during a game and to gain a deeper understanding of the role of affect and performance in collective team collapse situations, a quantitative field study was conducted during a preparation tournament with 75 male field hockey players of five teams and their five coaches. Players` running distance was recorded using GPS data. Pre-/post-competitive affect was assessed through the PANAS. Two third division teams of this sample, consisting of 33 athletes and their 2 coaches, reported to have experienced a naturally occurring collective team collapse in one of their games. Perceived team collapse games, where teams choked collectively, were compared to lost games, where a team was generally behind but did not report to have experienced a collective collapse. Results showed that running distance in perceived collective team collapse games was significantly lower than in lost games. Furthermore, although negative affect did not differ prior to a perceived collective team collapse game, negative affect was significantly higher after perceived collective team collapse games than after lost games. Negative affect and attempts to regulate the affective reaction are assumed to reduce athletes` performance capacity, resulting in a lower running distance. Negative affect and reduced performance are discussed to be mutually dependent in a dynamic process maintaining collective team collapse.